2013
DOI: 10.1002/2013wr014345
|View full text |Cite
|
Sign up to set email alerts
|

Retention and remobilization of colloids during steady-state and transient two-phase flow

Abstract: [1] In this work, we study colloid transport through a porous medium under steady-state and transient two-phase flow conditions. The porous medium was a PDMS micromodel and the immiscible fluids were water and fluorinert-FC43. Given that the micromodel was hydrophobic, fluorinert was the wetting phase, and water was the nonwetting phase. We used hydrophilic fluorescent microspheres (dispersed in water) with mean diameter of 300 nm. We directly observed colloid movement and fluids distribution within pores of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…The mathematical model described by Zhang et al . [] was employed to simulate the breakthrough curves (during steady state as well as transient flow) for both hydrophilic and hydrophobic colloids. The model is based on a coupled system of equations for two‐phase flow, advection‐dispersion of colloids, adsorption to and desorption from fluid‐fluid interfaces and fluid‐solid interfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mathematical model described by Zhang et al . [] was employed to simulate the breakthrough curves (during steady state as well as transient flow) for both hydrophilic and hydrophobic colloids. The model is based on a coupled system of equations for two‐phase flow, advection‐dispersion of colloids, adsorption to and desorption from fluid‐fluid interfaces and fluid‐solid interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zhang et al . [] conducted experiments on transport of hydrophilic particles (dispersed in water) during two‐phase flow in order to investigate how saturation change affects colloids retention and remobilization. The experiments were performed in a micromodel made of polydimethylsiloxane (PDMS) filled by water and fluorinert.…”
Section: Introductionmentioning
confidence: 99%
“…Colloid transport in a fluorocarbon‐water system was studied by Zhang et al . [], who used a hydrophobic micromodel, thereby making the fluorocarbon the wetting phase, and hydrophilic colloids were dispersed in the water phase. The authors found that at lower water saturation, more colloids were retained at the fluorocarbon‐water interface and the fluorocarbon‐water‐solid contact lines.…”
Section: Colloid Transport In Single Pore and Pore Network Micromodelsmentioning
confidence: 99%
“…Micromodels have been mostly used in studying displacements of two immiscible fluid phases in porous media [ Avraam et al ., ; Baouab et al ., ; Chang et al ., ; Corapcioglu et al ., ; NagaSiva et al ., ; Blois et al ., ; Zhang et al ., ]. Processes of drainage and imbibition, as well as the mechanisms that dominate them, like viscous or capillary fingering and snap‐off, have been studied using micromodels [ Zhang et al ., ; Ferer et al ., ; Grate et al ., ; Gutiérrez et al ., ; Hug et al ., ; Rangel‐German and Kovscek , ; Huh et al ., ].…”
Section: Introductionmentioning
confidence: 99%